1995
DOI: 10.1128/aac.39.3.598
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of murine invasive candidiasis with fluconazole and amphotericin B

Abstract: A study was performed to assess the in vivo relevance of the in vitro antagonism between fluconazole and amphotericin B against Candida albicans. Combinations of fluconazole and amphotericin B were explored for their efficacies against acute (100% mortality in 2 to 5 days) or less acute (100% mortality in 30 days) invasive candidiasis infections in mice with healthy immune systems and immunocompromised mice. Treatment efficacy was assessed by protection from mortality and/or a reduction in the fungal burden in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
3
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 24 publications
0
67
3
2
Order By: Relevance
“…[15] The mice were infected by injection of this inocula into a lateral tail vein. [2,3,15] Amphotericin B (Fungizone, Bristol-Myers Squibb), and fluconazole (Triflucan 100mg, Pfizer) were used, and prepared for injection as recommended by the manufacturer and terbinafine (Lamsil, Novartis) dissoluting in polyethylene glycol 200 and diluted in sterile distilled water. [17,18] The MICs for amphotericin B, fluconazole and terbinafine were determined by the broth microdilution method described by the National Committee for Clinical Laboratory Standards M27 A.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15] The mice were infected by injection of this inocula into a lateral tail vein. [2,3,15] Amphotericin B (Fungizone, Bristol-Myers Squibb), and fluconazole (Triflucan 100mg, Pfizer) were used, and prepared for injection as recommended by the manufacturer and terbinafine (Lamsil, Novartis) dissoluting in polyethylene glycol 200 and diluted in sterile distilled water. [17,18] The MICs for amphotericin B, fluconazole and terbinafine were determined by the broth microdilution method described by the National Committee for Clinical Laboratory Standards M27 A.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Amphotericin B has traditionally been considered the cornerstone of therapy for deep-seated fungal infections and fungemia, but it has toxic side effects. [1][2][3][4] Despite advances, antifungal therapy with amphotericin B, the azoles or flucytosine has not been uniformly successful. Problems with toxicity, the emergence of resistant strains of Candida spp.…”
Section: Sonuçmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option in renal failure is liposomal amphotericin B, but penetration of lipid form in renal tube is less and its efficacy on Candidal UTI is questionable (32). Although, fluconazole could be added to amphotericin B in case of renal failure or resistant organisms, it should be choosen as initial therapy for susceptible organisms (33)(34)(35)(36). When non-albicans Candida is probable, fluconazole is not as effective as amphotericin B (37).…”
Section: Managementmentioning
confidence: 99%
“…76 Sugar et al found the combination of fluconazole and amphotericin B was not antagonistic in vivo in mice with invasive candidiasis and suggested combination therapy be considered in management of clinical candidiasis. 77 Walsh et al reported that in-vitro combinations of amphotericin B and antifungal azoles were synergistic, additive, or indifferent in their interaction against P. boydii and antagonism was hot observed. 78 Combinations of antifungal drugs have proven to be the most effective approach for treating cryptococcal meningitis.…”
Section: Drug Combinationsmentioning
confidence: 99%